2022
DOI: 10.1073/pnas.2117553119
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell–resolution map of human retinal pigment epithelium helps discover subpopulations with differential disease sensitivity

Abstract: Significance Retinal degenerative diseases affect specific regions of the retinal pigment epithelium (RPE), suggesting the presence of functionally different RPE subpopulations. To identify these subpopulations in human eyes, we generated the first complete morphometric map of the RPE at single-cell resolution using artificial intelligence–based software. We identified five concentric RPE subpopulations, including a ring of RPE cells with cell area similar to macula in the periphery of the eye. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 47 publications
10
60
0
Order By: Relevance
“…Overall, these results confirmed that the ABCA4 LOF does not affect the ability of iPSCs to differentiate into mature and functional RPE cells. A comprehensive single-cell-resolution morphometric analysis of iRPE lines was performed to determine potential changes in iRPE cell shape metrics caused by ABCA4 LOF ( Ortolan et al., 2022 ). STGD1-iRPE did not show any significant differences compared with control-iRPE on four distinct morphometric features that define compact packing of epithelial cells in a sheet—cell area, aspect ratio, hexagonality, and the number of neighbors ( Figures S3 G–S3J).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these results confirmed that the ABCA4 LOF does not affect the ability of iPSCs to differentiate into mature and functional RPE cells. A comprehensive single-cell-resolution morphometric analysis of iRPE lines was performed to determine potential changes in iRPE cell shape metrics caused by ABCA4 LOF ( Ortolan et al., 2022 ). STGD1-iRPE did not show any significant differences compared with control-iRPE on four distinct morphometric features that define compact packing of epithelial cells in a sheet—cell area, aspect ratio, hexagonality, and the number of neighbors ( Figures S3 G–S3J).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to existing evidence for topographical differences in hRPE cellular and molecular features (for example, comparing peripheral with macular tissue; see Table S1 ), a recent study revealed regional heterogeneity and cellular mosaicism based on surveying hRPE cell morphology over the entire posterior eye [ 119 ]. The multiple RPE subpopulations identified by scRNA-seq in both the human and mouse raises the possibility that transcriptomic differences underlie this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The m.3243A>G mutation causes a characteristic macular atrophy (Figure 1A). It has been hypothesized that the unique macular specificity in this disease is caused by region-specific dysfunctional RPE cells (56). Another notable anatomical feature of retinal dystrophy caused by m.3243A>G is the presence of outer retinal tubulations (ORT) (24, 37, 38), indicating outer retinal dysfunction and Müller cell activation (49).…”
Section: Discussionmentioning
confidence: 99%